2015
DOI: 10.1016/j.chemosphere.2014.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cypermethrin on avoidance behavior, survival and reproduction of Folsomia candida in soil

Abstract: Cypermethrin is a pyrethroid widely used in agriculture and in control of animal ectoparasites, being effective against a large number of insects. Therefore, this study aimed to evaluate the effects of cypermethrin on soil fauna using reproduction and behavior ecotoxicological tests with the springtail Folsomia candida. The surface layer of a soil characteristic of the western region of the Santa Catarina State, classified as Typic Dystrupept, was used as test substrate. The treatments on both tests consisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 20 publications
0
13
0
2
Order By: Relevance
“…Because the raising of livestock is important to several countries in Latin America, more research is needed on this important topic. The study of Zortea et al , carried out in Brazil, found toxic effects of cypermethrin in reproduction and avoidance tests with F. candida in natural soils, in doses similar to those recommended for use on poultry beds, which can indicate impacts on soil fauna.…”
Section: Chemical Use and Impacts On Soils In Latin Americamentioning
confidence: 90%
See 1 more Smart Citation
“…Because the raising of livestock is important to several countries in Latin America, more research is needed on this important topic. The study of Zortea et al , carried out in Brazil, found toxic effects of cypermethrin in reproduction and avoidance tests with F. candida in natural soils, in doses similar to those recommended for use on poultry beds, which can indicate impacts on soil fauna.…”
Section: Chemical Use and Impacts On Soils In Latin Americamentioning
confidence: 90%
“…Toxicity tests with F. candida and insecticides indicate that F. candida is more sensitive when exposed to current recommended dosages (except for a green formicide ) than earthworms , with stronger effects on reproduction than on avoidance . Only 2 references were found for enchytraeids ( E. crypticus ), and the results suggest that this species is less sensitive to insecticides than either F. candida or E. andrei .…”
Section: Chemical Use and Impacts On Soils In Latin Americamentioning
confidence: 92%
“…Several methods are used to control mealworms, being the use of chemical insecticides based on pyrethroids or organophosphates the main method employed. However, these drugs have limited efficiency and present a risk for meat contamination [9,18]. Study revealed that cypermethrin used in the control of mealworm exerts negative effects on the survival and reproduction of springtails [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, these drugs have limited efficiency and present a risk for meat contamination [9,18]. Study revealed that cypermethrin used in the control of mealworm exerts negative effects on the survival and reproduction of springtails [18]. Thus, is important the search of new methods to control the mealworm [2].…”
Section: Introductionmentioning
confidence: 99%
“…Cypermethrin is the main insecticide used to control A. diaperinus; however, this drug may be toxic to the soil fauna (Styrishave et al, 2010;Zortéa et al, 2015), and consequently cause environmental damage. Therefore, it is important to evaluate the environmental impact of new treatments because contamination may affect many ecology systems.…”
Section: Melaleuca Alternifolia Essential Oil Against the Lesser Mealmentioning
confidence: 99%